Failure analysis of S135 drill pipe body fracture in a well. (March 2023) - Shen, Dan; Tong, Ke; Fan, Zhi-hai; Yang, Wen-zhe; Liu, Qing; Li, Hong; Zhao, Jin-lan; Cong, Shen
Abstract: During the operation of a well in Xinjiang, a drill pipe body fracture accident occurred. The cause of the fracture failure of this S135 drill pipe body was investigated through chemical analysis, mechanical property testing, metallurgical examination, analysis at the fracture, simulated heat treatment test and finite element analysis combined with the site operation. The results show that the abnormal structures and coarse grains of bainite and ferrite appear locally due to the factors such as uneven heat treatment in the production process of the drill pipe body, which decreases the strength of the abnormal area of the structure, and finally leads to the overload failure of the drill pipe at the abnormal part of the pipe body when the drill pipe is stuck under load.